Paroxysmal Sympathetic Hyperactivity in Patients Victims of Traumatic Brain Injury: Literature Review - Kalkmann, Gabriela Ferreira; Crestani, Letícia Novak; Santos, Letícia Adrielle dos; Pereira, Carlos Umberto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
The present literature review aims to present the physiology of paroxysmal sympathetic hyperactivity (PSH) as well as its clinical course, conceptualizing them, and establishing its diagnosis and treatment. Paroxysmal sympathetic hyperactivity is a rare syndrome, which often presents after an acute traumatic brain injury. Characterized by a hyperactivity of the sympathetic nervous system, when diagnosed in its pure form, its symptomatologic presentation is through tachycardia, tachypnea, hyperthermia, hypertension, dystonia, and sialorrhea. The treatment of PSH is basically pharmacological, using central nervous system suppressors; however, the nonmedication approach is closely associated with a reduction in external stimuli, such as visual and auditory stimuli. Mismanagement can lead to the development of serious cardiovascular and diencephalic complications, and the need for neurosurgeons and neurointensivists to know about PSH is evident in order to provide a fast and accurate treatment of this syndrome.
Keywords: autonomic nervous system; craniocerebral trauma; primary dysautonomias